Some Curious Phases of the Railway Question in Europe - Sterne, Simon (Quarterly Journal of Economics, 1887)
Journal Article Some Curious Phases of the Railway Question in Europe Get access Simon Sterne Simon Sterne Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 1, Issue 4, July 1887, Pages 453–468, https://doi.org/10.2307/1879340 Published: 01 July 1887